Patients' experiences of nurses' heartfelt hospitality as caring: A qualitative approach. Issue 11 (13th November 2018) - Kelly, Rosalind; Wright‐St Clair, Valerie; Holroyd, Eleanor
Abstract: Aims and Objectives: To answer the question "What is the lived experience of hospitality during a patient's hospital stay for elective surgery?" Background: Hospitality centres on a host offering comfort to others, as in a personal care context. Caring constitutes the essence of what it is to be human, having a profound effect on well‐being and recovery from surgery. Caring is one of the most elusive and diversely contested concepts in nursing; however, care provided by nurses seldom transcends as deep human connections and social utility. This study explored the nature, meaning and experience of hospitality as care from the perspective of elective surgery patients. Consolidated Criteria for Reporting Qualitative criteria were used. Design: A hermeneutic phenomenological methodology. Methods: Data were gathered through semi‐structured, face to face interviews with seven patients from both private and public hospitals, and from different cultural backgrounds. Results: Three interpretative notions were as follows: experiences of hospitality as feeling "really" cared for, being at ease and being healed. Hospitality exists in the receiver's lived experience, evoking a special moment which leads to feelings of great comfort and feelings of being truly cared about. When hospitality is received, patients feel a connection; they begin to trust and their healing begins. Conclusion: The offering of often small, yet heartfelt acts of hospitality, indicated that nurses can evoke powerful lived experiences which benefit patients undergoing elective surgery. Relevance to clinical practice: The importance of prioritising emotional and social connections to the hospitality experience needs emphasis at all levels of the clinical structure. Hospitality as caring needs to form a part of all undergraduate and postgraduate nursing curricula, and ongoing professional development. The participant quotes presented in this article could form exemplars for the provision of hospitable nursing care practices, highlighting nurses getting to know and understand their patients, and being interested in their lives.